Hadith And Literature: Hadith Reception in LIIA Rhyme as Transmission of Ma'rifatullah Hamzah Fansuri - Ubaidillah Ubaidillah; Nurul Azizah (Dialogia: Islamic Studies and Social Journal, 2021)
Transmission of Islamic knowledge should be important to pay attention to local wisdom as a medium for da'wah so that amar ma'aruh nahi mungkar is not limited to the material message but also in the process and packaging. This is where Islam must be interpreted as a methodological tool as well as a value system concerning the dialogical dimension of man's love for God. This research is a literature study using the living hadith study method by focusing on verse verses with tauhid nuances as the basis of the teachings of Hamzah Fansuri's wihdatul wujud. This study aims to explain how the hadith receptions in tauhid sentences and how Hamzah Fansuri came to the meaning of LIIA as a tauhid system and how the position of LIIA-themed poetry in perahu poetry. The result, first, LIIA's poetic poetry media is a reception of a Sufistic hadith as a way of capturing the bathiniyyah feeling of the unity of man and God. second, LIIA's poetry is an influence from the literary form to further explain my relationship with the Beloved. third, LIIA poetry in the verse of the perahu is more as a methodology of preaching about wihdatul wujud to awaken the passion of human love for god which is transcendental